A case of pharmacist-led care team interventions to maximize rural patient quality of life - Megan Undeberg; Kimberly McKeirnan; David Easley; Kyle Frazier (Elsevier, 2021)
A 64-year-old rural home bound patient in Washington State was identified to be at increased risk for negative health care outcomes related to chronic end kidney disease and poorly controlled diabetes. The patient lacked understanding of the use of monitoring equipment as well as diabetes education to improve quality of health; he also did not have access to medical supply equipment. A pharmacist-led care team comprised of a pharmacist, a community health worker, and a home health nurse implemented comprehensive medication review techniques as well as direct patient care education to engage the patient in managing his health. Involvement with this home visit care team combined with the patient's recently developed interest in managing his health re-engaged the patient. He began attending more frequent visits with his providers and increased his interest in meeting with a diabetes educator at the local clinic. Resulting interactions with the patient's providers, pharmacy, and community resources increased patient's compliance, access to specialists of care, and in-home safety measures. Factors contributing to poorer overall health and higher rates of death among rural patients include increased travel time to health care facilities and providers, higher rates of unhealthy lifestyle choices such as cigarette smoking and obesity, higher rates of poverty and less access to healthcare in general. This scenario emphasizes the important role an interprofessional team plays in the care of isolated, rural health patients in managing chronic disease states for stability as well as quality of life.